Comparison of Community Rehabilitation Services for the Elderly in South Korea and Japan: Focusing on the Long-Term Care Insurance System - Minyoung Lee (Korean Research Society of Physical Therapy, 2022)
Background: As South Korea enters an aged society, the government has emphasized the need for a soft landing of the older adults into the community after the acute and recovery periods under a national policy of "community care." However, the institutionalization of community rehabilitation services to implement this is insufficient. Japan had already entered an aged society when the Long-Term Care Insurance System was introduced in 2000. Thus, the case of Japan's institutionalization of the system is expected to have implications for us in supplementing a suitable system for the aged society.Objects: This study compared the institutionalization process of the Long-Term Care Insur-ance System in South Korea and Japan and the services currently being implemented in each country.Methods: To examine the institutionalization process and services of the system, related legal rules and regulations, government reports, and articles were reviewed. To examine the operation status of the system, statistical data provided by each country's government were analyzed.Results: Japan recognized the importance of community rehabilitation even before the en-actment of Long-Term Care Insurance. Thus, community rehabilitation services, such as home-visit rehabilitation and health facilities, were already stipulated in the law. Under such institu-tional legacy, Long-Term Care Insurance was able to establish a service system, which balanced welfare and health-related services, including various types of services with enhanced reha-bilitation functions. In South Korea, rehabilitation policies were not much considered in the process of institutionalizing the system; thus, it was composed mainly of services focusing on care and recuperation. Conclusion: In order to realize community care, rehabilitation services need to be developed in Long-Term Care Insurance System in various forms such as home-visit services, daily services, short stay, and facility services.